INTEGRATIVE ESSENCE OF TECHNOLOGIES INNOVATIVE EDUCATIONAL PROCESS - Sariyev Rustam Bobomuradovich (International Engineering Journal For Research & Development, 2020)
Presentation of educational technologies in practice. Characteristic features of educational technologies. The main functions of educational technologies.The technological level of education and their types.Multifactoriality and content diversity of pedagogical processes.The developing nature of modern educational technologies.